One-Way Valve as Management of Chest Tube Ambulation in Pneumothorax Cases - Junaidi, Katerine; Oea Khairsyaf; Fenty Anggrainy; Deddy Herman (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
An adequate chest drainage system is the main goal of fluid and air evacuation and restoring negative pressure intrapleural so it can help lung development. The intrapleural is a closed, airtight space filled with a small amount of fluid as a lubricant for lung movement during the breathing process. Accumulation of intrapleural air is known as pneumothorax, and one of the initial management options is the implantation chest tube. Chest tubes, which are connected to a water seal, conventionally show varying results and have shortcomings because they require monitoring and limit patient mobility, so the safety of their use in outpatient settings is questionable. Lungs that are not inflated or have an inflated water seal still show air bubbles even though it has been installed. A chest tube adequate for 48 hours is a condition known as persistent air leak, thus requiring extended usage time from chest tube to the drainage management complex. Use of ambulation management through the use of various tools and equipment devices which can be connected with a chest tube can be an option with the aim of reducing treatment time, lowering funding, increasing comfort and hopefully providing better external results.